Russian as a Foreign Language: Teaching Reading - Akhmedov B.Y. (Indonesian Journal of Innovation Studies, 2022)
Reading is one of the types of speech activity associated with the perception and comprehension of written speech. However, reading contributes to thedevelopment of all types of speech activity. We rely on reading in the developmentand improvement of listening and speaking skills, in teaching students writing.